2018
DOI: 10.1016/j.ecoenv.2018.07.092
|View full text |Cite
|
Sign up to set email alerts
|

Salinity alleviates zinc toxicity in the saltmarsh zinc-accumulator Juncus acutus

Abstract: The potential importance of Juncus acutus for remediation of Zn-contaminated lands has been recognized, because of its Zn tolerance and capacity to accumulate Zn. Since it is also a halophyte, the extent to which salinity influences its Zn tolerance requires investigation. A factorial greenhouse experiment was designed to assess the effect of NaCl supply (0 and 85 mM NaCl) on the growth, photosynthetic physiology and tissue ions concentrations of plants exposed to 0, 30 and 100 mM Zn. Our results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…These benefits induced by EBR enhanced pigment biosynthesis and promoted a positive impact on the photosynthetic apparatus. Mateos-Naranjo et al (2018) found reductions in Chl a, Chl b and Car levels in Juncus acutus plants exposed to Zn toxicity (100 mM Zn). However, Ramakrishna and Rao (2015) demonstrated that foliar application of EBL and HBL at concentrations of 0.5, 1.0 and 2.0 μM effectively alleviated the deleterious effects of Zn toxicity on Raphanus sativus, protecting mainly the chloroplast membranes and increasing Chl a, Chl b and Car.…”
Section: Ebrmentioning
confidence: 87%
“…These benefits induced by EBR enhanced pigment biosynthesis and promoted a positive impact on the photosynthetic apparatus. Mateos-Naranjo et al (2018) found reductions in Chl a, Chl b and Car levels in Juncus acutus plants exposed to Zn toxicity (100 mM Zn). However, Ramakrishna and Rao (2015) demonstrated that foliar application of EBL and HBL at concentrations of 0.5, 1.0 and 2.0 μM effectively alleviated the deleterious effects of Zn toxicity on Raphanus sativus, protecting mainly the chloroplast membranes and increasing Chl a, Chl b and Car.…”
Section: Ebrmentioning
confidence: 87%
“…Among specific tolerance mechanisms, it is well recognized that halophytes use osmoprotective and ion-detoxification strategies [3][4][5] to regulate their tissues' Na concentration patterns or K/Na ratio variations [2]. Many studies have been carried out to evaluate the effect of salt excess carboxylation capacity and energy use efficiency in halophytes [6][7][8][9][10][11][12], showing how these plants are able to maintain metabolic processes despite being exposed to high salt concentration. However, studies focused on the effect of salt on xylem anatomy and functioning, plant-water relations, and photosynthetic capacity are scarce [13], despite the relevance of these traits to determine plant tolerance to environmental stress [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This species has been widely studied for its capacity of Zn tolerance and accumulation in land contaminated with this metal. Mateos-Naranjo et al (2018) studied the effect on this hydrohalophyte of NaCl at concentrations representative of estuarine environments. Salt considerably reduced the harmful effects of high Zn concentrations on the growth and development of this halophyte.…”
Section: Hydrohalophyte Speciesmentioning
confidence: 99%